Interactions of the chemokines CXCL11 and CXCL12 in human tumor cells - Christian Koch; Nina Charlotte Fischer; Malte Puchert; Jürgen Engele (BMC Cancer, 2022)
Abstract Background The chemokines, CXCL12 and CXCL11, are upregulated in tumors from many organs and control their progression. CXCL12 and CXCL11 affect tumor cell functions by either binding their prime receptors, CXCR4 and CXCR3, respectively, and/or CXCR7 as a common second chemokine receptor. In humans, CXCR3 exists in the functional splice variants, CXCR3A and CXCR3B, which either have pro- or anti-tumor activity, respectively. Despite the intimate crosstalk between the CXCL12- and CXCL11-system, the impact of a combination of CXCL12 and CXCL11 on tumor progression remains vague. Methods In the present work, we have analyzed CXCL12 and CXCL11 for combined effects on migration, invasion, proliferation, and cytostatic-induced apoptosis of the human tumor cells, A549, A767, A772, DLD-1, and MDA-MB-231. Results We demonstrate that the mode of interaction differs with respect to cell type and function and allows for either potentiation, attenuation or no changes of cellular responses. The divergent responses are not the result of the distinct use of different CXCL12- and CXCL11-receptors by the respective tumor cells, but in case of cell migration seem to be associated with the activation of p38 signaling pathways. Conclusions Our findings point to therapeutic limitations of ongoing efforts to selectively target CXCR3, CXCR4, or CXCR7 in cancer patients, and rather favor individualized targeting strategies.